2015
DOI: 10.1002/jsfa.7471
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of degree of milling on the appearance and aroma characteristics of raw rice

Abstract: The present study demonstrated that sensory impacts of DOM on raw rice were present between brown rice and milled-rice samples, but not among the milled-rice samples varying in SLC level from 0.64% to 0.25%. The overall findings indicate that consumers may not detect appearance- or aroma-related differences among raw-rice samples ranging in SLC from 0.64% to 0.25%. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…In addition, for the burlap flavor attribute often found in brown rice (Billiris et al, ), the JAS_F sample (milled jasmine‐rice) was rated as the most intense among the eight samples, including the two brown‐rice samples in the UAS condition, while the JAS_F sample as well as other milled‐rice samples were rated less intense than the brown rice sample (BRO_G) for the RAS condition. Since the burlap aroma/flavor attribute mainly results from rice bran (Rodríguez‐Arzuaga et al, ), the attribute‐intensity was found to be greater in brown rice than in highly milled rice, so the RAS seems to perform better in evaluating cooked rice with respect to the burlap flavor attribute. Finally, six milled‐rice samples showed significantly greater intensities of the floral flavor attribute than brown rice samples under both the UAS and the RAS conditions; this is to some extent in line with the previous finding that a deep milling process resulted in a greater intensity of floral flavor (Champagne et al, ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, for the burlap flavor attribute often found in brown rice (Billiris et al, ), the JAS_F sample (milled jasmine‐rice) was rated as the most intense among the eight samples, including the two brown‐rice samples in the UAS condition, while the JAS_F sample as well as other milled‐rice samples were rated less intense than the brown rice sample (BRO_G) for the RAS condition. Since the burlap aroma/flavor attribute mainly results from rice bran (Rodríguez‐Arzuaga et al, ), the attribute‐intensity was found to be greater in brown rice than in highly milled rice, so the RAS seems to perform better in evaluating cooked rice with respect to the burlap flavor attribute. Finally, six milled‐rice samples showed significantly greater intensities of the floral flavor attribute than brown rice samples under both the UAS and the RAS conditions; this is to some extent in line with the previous finding that a deep milling process resulted in a greater intensity of floral flavor (Champagne et al, ).…”
Section: Resultssupporting
confidence: 89%
“…Uncooked and cooked rice samples are examples that represent such limitations of the universal scale. More specifically, in previous studies that used the UAS as a quantitative reference for descriptive sensory analyses of uncooked (Rodríguez‐Arzuaga et al, ) and cooked (Champagne et al, ; Meullenet et al, ) rice samples, the highest intensity ratings for most attributes were generally lower than 3.0‐point on the scale ranging from 0 to 15. Using this method, most attributes of aromas and flavors showed no significant differences between cooked rice samples evaluated in such previous studies (Champagne et al, ; Meullenet et al, ; Rodríguez‐Arzuaga et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Obviously, milled rice had significantly greater L * value than brown rice (Rodríguez‐Arzuaga, Cho, Billiris, Siebenmorgen, & Seo, ), and the lightness increased with increasing DOM (Monks et al., ; Figure ). Choi, Seo, K. Lee, S. Lee, and J. Lee, , ) observed that the L * , a * , and b * values were significantly greater as DOM increased in black rice, regardless of cultivars.…”
Section: Effects Of Milling On Rice Grain Qualitymentioning
confidence: 99%
“…Recently, Rodriguez-Arzuaga et al [53] reported that, DOM affects raw-rice appearance and aroma-related attributes. Likewise, the study conducted by Griglione et al [54] reported that the storage temperature (5°C vs 25°C) does not significantly influence aroma preservation and they also reported that, heptanal/1-octen-3-ol and heptanal/octanal were act as indices of aroma quality for the Italian cultivars investigated and more in general, of rice aroma quality. In this way, lots of environmental attributes affects the aroma of rice.…”
Section: Environmental Effect On Fragrancementioning
confidence: 84%